PEMBUATAN DAN PENGUJIAN ASAP CAIR DARI TEMPURUNG KELAPA DAN TONGKOL JAGUNG SEBAGAI BAHAN PENGAWET IKAN - Mentari, Eka Pratiwi; Sahara, Sahara (Universitas Islam Negeri Alauddin Makassar, 2017)
This study aims to find out the mass of coconut shell charcoal and corn cobs mass with the volume of liquid smoke produced, the utilization of liquid smoke from coconut shell and corn cob so that it can be used as fish preservative and fish quality resulting from addition of liquid smoke process. The parameters measured in this study were the ratio of mixture of the number of coconut shell and corn cob, the test of liquid smoke produced. The tested parameters of quality resulting from liquid smoke are seen from the smell, texture, color, odor and taste of the fish so that bias is said to be a good fish preservative with conventional breathing, immersion with liquid smoke and salt water immersion. Filtration using active Zeloit tools as well as Activated Carbon. Based on the results of the comparison of the material with the volume of liquid smoke produced from coconut shell and corn cob with each mass 7000 gr, 8000 gr, and 15000 gr is 200 ml, 210 ml, 500 ml. And for testing that is that fish that use conventional curing can survive with long and good result.Â Keywords: Conventional fumigation, active zeloit substances, activated carbon substances, and cork fish.